The operational mode of revenue management - Chaika, Tatiana; Sanina, Arina; Tretiakova, Kateryna (European Open Science Space, 2025)
The paper examines the role of the operational mode of the Revenue Management system in organizing a continuous and adaptive income management process. The main focus is on the key characteristics of the Revenue Management system's operational mode: dynamic nature, cyclicality, data-driven management, hierarchical coordination, adaptability, and the balance of automation and human control.
Keywords: revenue management system; operational mode; dynamic pricing; cyclicality; iterativity